Perbandingan Metode Gaussian Filter dengan Median Filter dalam Mereduksi Noise Pada Citra Digital - Panji Novantara; Jajang Mutiara (JEJARING : Jurnal Teknologi dan Manajemen Informatika, 2021)
Basically all humans want something perfect as well as in a digital image. One problem that often occurs in the digital image is noise or damage on the image. Noise is an error that occurs in the process of shooting so that unwanted signals exist. Improvement of digital images containing noise is an important thing in digital image processing. In designing the applications, the writer uses two methods i.e. Gaussian filter and Median Filter methods. Gaussian filter method is a linear filter with a weighted value for each pixel members is selected based on the shape of the members’ function. While the median filter method is one of the non-linear filter methods that arranges a bunch of pixel intensity values then replaces the pixel values being processed with a median value. From the test results of a digital image that has a noise, it is known that the result of the median filter method is better than Gaussian filter to reduce noise in digital images.Key words: Image Filtering, Method Gaussian Filter, Median Filter